Some basic properties of Hadamard groups - Merza, Melinda V. (Animo Repository, 1996)
Let G be a finite group of order 2n with a subset D and an element e prime such that / D / = n and(1) / D intersect Da / = n if a = e 0 if a = e prime n/2 if a is not equal to e, e prime, a membership G(2) / Da intersect &b, be prime / = 1 for any elements a and b of G. Then G is called an Hadamard group. This thesis is a detailed study about some of the basic properties of Hadamard groups. This is based on the paper of Noboru ito entitled On Hadamard Groups which appeared in the Journal of Algebra, Volume 168, Number 3 on September 15, 1994.